Correction: A cross-linkable hole transport material having improved mobility through a semi-interpenetrating polymer network approach for solution-processed green PHOLEDs. Issue 45 (6th November 2018) - Park, So-Ra; Kang, Ji-Ho; Ahn, Dong A.; Suh, Min Chul
Abstract : Correction for 'A cross-linkable hole transport material having improved mobility through a semi-interpenetrating polymer network approach for solution-processed green PHOLEDs' by So-Ra Park et al., J. Mater. Chem. C, 2018, 6, 7750–7758.